Cuproptosis in hepatocellular carcinoma: bridging copper homeostasis with therapeutic horizons - Songsong Fan; Aoqing Wang; Rui Peng; Jun Cao; Daoyuan Tu; Bingbing Su; Jiahao Zhang; Shengjie Jin; Guoqing Jiang; Chi Zhang; Dou-Sheng Bai (Molecular Biology Reports, 2026)

Synergistic dual-site passivation via ionic liquid engineering for efficient and stable deep-red CsPbI₃ QLEDs - Xiaoke Li; Jinjian Lu; Rui Han; Xiaoqing Jing; Yuyu Zhang; Jintao Wang; Ren Sheng; Ping Chen (Chemical Engineering Journal, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

A synthetic microbiome drives a multi-omics response to remediate 1,4-dithiane–contaminated soil and simultaneously suppresses antibiotic resistance genes - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Journal of Hazardous Materials, 2026)

TMF: Temporal multi-modal fusion framework for estimating wheat yield from multi-source satellite and environmental data across the European Union - Zhixian Lin; Sheng Wang; Kaiyu Guan; Jiaying Zhang; Senthold Asseng; René Gislum; Jørgen Eivind Olesen; Klaus Butterbach-Bahl; Miroslav Trnka; Rui Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Effect of first-stage anode axial position on discharge characteristics of a double-stage anode layer thruster - Rui Ding; Sheng Wen; Zhihao Liu; Jia Liu; Guanrong Hang; Yan Zhang; Ximing Zhu; Yongjie Ding (Advances in Space Research, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Six-component load reconstruction for offshore wind turbine blades considering deformation-induced additional moments - Baoxuan Wang; Xu Liang; Lizhong Wang; Fangyuan Sheng; Xiang Wang; Yue Chen; Jianwei Zhang; Shengjie Rui; Rui Liu (Ocean Engineering, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Bimetallic sulfide catalysts photocatalytically reduce carbon dioxide into high-value fuels: A review - Chenyue Hua; Kai Xie; Cheng Peng; Jiang Wu; Sheng Wang; Jingxin Xu; Kai Huang; Xueli Sun; Hai Zhang; Rui Zhu; Ping He; Ahmad Hosseini-Bandegharaei (Journal of Environmental Chemical Engineering, 2026)

Advances and challenges in multi‑scale water environment system modeling: from process simulation to a novel simulator architecture - Rui Xia; Sheng Chen; Yan Ding; Mingdong Sun; Yali Wu; Kaifang Shi; Yajing Cai; Kai Zhang; Yan Chen; Lei Zou (Ecological Modelling, 2026)

Human Umbilical Cord-Derived Mesenchymal Stem Cells-Involved Strategies: Advancing Tendon Injuries Therapy Towards Clinical Translation - Mumin Cao; Mengze Tong; Yunmeng Pu; Xuepeng Lv; Yimin Sun; Haoyu Zhang; Renwang Sheng; Hao Wang; Yucheng Gao; Guangchun Dai; Fei Xiong; Qianqian Wang; et al. (Stem Cell Reviews and Reports, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Evolution of soil arching under different initial water-saturation conditions via coupled SPH-DEM method - Rui-Xiao Zhang; Dong Su; Xiang-Sheng Chen; Xiu-Song Shi; De-Jin Zhang (Computers and Geotechnics, 2026)

A bead-based dendritic amplification system for multiplex miRNA detection - Feiyang Qian; Rui Zhu; Yao Lu; Tenghua Zhang; Yuqing Zhu; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Navigational path optimization methodology for wing-diesel hybrid ship based on improved Double Deep Q-Network - Cong Wang; Lianzhong Huang; Ranqi Ma; Kai Wang; Jinlu Sheng; Zhang Ruan; Rui Zhang; JianLin Cao (Ocean Engineering, 2025)

Flame characteristics and explosion risk of hydrogen-blended natural gas pipeline leakage under high-pressure and high-equivalence-ratio environments - Sheng Qi; Yuntao Li; Wenhao Zhang; Dan Wang; Rui Zhou; Qi Jing; Lei Cheng; Zhou Wang (Fuel, 2025)

Self-assembling metal–polyphenol–protein nanocomplex enhancing islet graft survival and transplantation outcome - Zeqing Wang; Yixuan Zhu; Huixiang Sheng; Yang Cheng; Ying Zhang; Yifei Yang; Zhuoxun Huang; Xiaoyue Chen; Yifan Qiu; Rui Wu; Di Huang; Wenjing Gong; et al. (Chemical Engineering Journal, 2025)

Chemical constituents of Tinospora hainanensis and their chemotaxonomic significance - Ming-Hua Wang; Rui Ao; Bao-Qiang Liu; Juan Zhang; Jun-Sheng Zhang (Biochemical Systematics and Ecology, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Real-time rockburst warning using microseismic multi-feature parameters based on the PSO-GRNN model - Wen Xuan Dong; Qing He Zhang; Xiao Rui Wang; He Peng Dong; Chuan Bing Wang; Sheng tao Wang (Natural Hazards, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Dynamic response of ceramic-reinforced metallic corrugated sandwich structures under combined blast-fragment loading - Chang-ye Ni; Cong Luo; Lu-sheng Qiang; Xin-yi Bai; Jia-le Wu; Jian-hong Zhang; Rui Zhang (Engineering Structures, 2025)

Novel laser-driven fast pyrolysis of biomass: Insights into biochar characteristics and applications - Rui Ma; Jintao Luo; Xiaoning Duan; Yuwan Sheng; Shaohui Wang; Deli Zhang; Fang Wang; Shuo Yang; Weiming Yi (Bioresource Technology, 2025)

Theoretical calculation model of the soil arching effect considering tunnel influence - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Xiang-Sheng Chen (Tunnelling and Underground Space Technology, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Cascade-targeting hydrogel microspheres with biomimetic nanoparticles enable multifaceted anti-inflammatory and antioxidant defense for osteoarthritis management - Shengli Ma; Yuqiao Sheng; Chaoyang Zhang; Feng Li; Na Wei; Jingjing Xu; Rui Xue (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficient solar-driven tandem catalysis for biomass valorization: selective C C bond cleavage to synthesize xylitol - Liangdong Hu; Huiyan Zhang; Zupeng Chen; Nengchao Luo; Lian-Hua Xu; Kai Wu; Longfei Hong; Sheng Chu; Rui Xiao (Science Bulletin, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Comparative metagenomic analyses of viral genomic diversity and ecosystem functions in extremely acidic copper mine tailings - Pei-Zhe Ye; Qiang Yang; Chu-Yi Zhang; Tao-Tao Yang; Sheng-Fang Jiang; Rui Lan; Shao-Ming Gao; Li-Nan Huang (Journal of Hazardous Materials, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Assessing the long-term impact of vegetation cover on sediment load within buffer zones of the upper Qin River Basin, Guangxi, China - Bin-rui Gan; Sheng-fa Yang; Wen Zhang (Environmental Fluid Mechanics, 2025)

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)

Identification and optimization of ecological corridors in the middle reaches of the Yellow River Basin - Sheng Wang; Rui Zhang; Jinfeng Wang; Qing Li; Rende Wang; Yangrong Li; Lixing Zhang (Journal of Cleaner Production, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

The Influence of Vickers Hardness and Brittleness on Particle Size Distribution During Ball Milling: A Multifractal Approach - Sheng Zhang; Yichao Rui; Zilong Zhou; Xin Cai; Hongzhi Cui (Rock Mechanics and Rock Engineering, 2025)

Isotope tracer study of soil erosion in a typical sub-watershed in the eastern Tianshan Mountains, China - Ninglu Zhang; Jianjun Yang; Wenli Xing; Xinyu Liu; Feifei Sheng; Wanqing Zhao; Zhiguang Zhang; Ziqi Tian; Rui Chen (Journal of Environmental Radioactivity, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Spatiotemporal analysis, simulation, and early warning of landslides based on landslide sensitivity and multisource precipitation products in Southwestern China - Rui Zhang; Sheng Chen (Landslides, 2025)

Solar-driven transient Lewis acid sites for synergistic efficient photocatalytic isomerization of glyceraldehyde - Liangdong Hu; Lian-hua Xu; Chenjun Yang; Longfei Hong; Kai Wu; Sheng Chu; Longlong Ma; Shurong Wang; Rui Xiao; Huiyan Zhang (Chemical Engineering Journal, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Mechanical properties and energy dissipation characteristics of oil-saturated sandstone under triaxial compression: an experimental investigation - Sheng Zhang; Rui Zhou; Xulong Zhang; Xiaoliang Wang; Guiwu Han (Bulletin of Engineering Geology and the Environment, 2025)

YOLO-RCS: A method for detecting phenological period of 'Yuluxiang' pear in unstructured environment - Rui Ren; Shujuan Zhang; Haixia Sun; Ning Wang; Sheng Yang; Huamin Zhao; Mingming Xin (Computers and Electronics in Agriculture, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

A new benzophenone derivative from Aspergillus fumigatus WJ-131 - Jia-Qi Liu; Sheng-Qi Zhang; Xiu-Hong Wu; Shuai-Xing Liu; Rui-Dang Yang; Liang Deng; Le Cai (Natural Product Research, 2025)

A new anti-inflammatory thujane monoterpenoid glycoside ester from Pittosporum heterophyllum Franch - Jia-Qi Ding; Sheng-Nan Guan; Yu-Feng Zhang; Zhao-Xuan Wang; Wei-Zhen Kong; Jun-Rui Ren; Xiu-Yun Zhang (Natural Product Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

A free radical interlocking co-deposition strategy based on the oxidative pyrolysis mechanism of polyethylene terephthalate to achieve green energy recovery - Weiwen Gu; Tianyi Ma; Xinyu Cui; Xiaoyu Gu; Jun Sun; Jinping Xiong; Rui Wang; Sheng Zhang (Journal of Hazardous Materials, 2024)

Preparation and properties of cationic starch-carrageenan‑sodium alginate hydrogels with pH and temperature sensitivity - Zheng Cai; Wei Zhou; Wenjing Chen; Rui Huang; Rui Zhang; Li Sheng; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Molecularly engineered chitosan-derived poly(aprotic/protic ionic liquids) double-network hydrogel electrolytes for flexible supercapacitors and wearable strain sensors - Hailiang Sheng; Rongli Li; Rui Li; Long Li; Shizhao Li; Yunqi Li; Jili Yuan; Jun Huang; Qinqin Xu; Qiang Zheng; Lihua Zhang; Haibo Xie (Chemical Engineering Journal, 2024)

Sesquiterpenes from Tinospora sinensis and their chemotaxonomic significance - Rui Ao; Ming-Hui Li; Zi-Nan Xiao; Xue-Lian Tang; Jun-Sheng Zhang; Hua Zhang (Biochemical Systematics and Ecology, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Neurotoxicity of tetramethylammonium ion on larval and juvenile zebrafish: Effects on neurobehaviors and multiple biomarkers - Ruixin Zhang; Rui Wang; Jiajun Chang; G. Daniel Sheng; Daqiang Yin (Journal of Environmental Sciences, 2024)

The premixed flame structure and combustion mechanism of clean hydrogen mixed with multi-component natural gas - Sheng Qi; Yuntao Li; Shuo Zhou; Qi Jing; Laibin Zhang; Rui Zhou; Wanyun Chen; Tong Li (Fuel, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

A novel cooperative optimization method of course and speed for wing-diesel hybrid ship based on improved A* algorithm - Cong Wang; Lianzhong Huang; Ranqi Ma; Kai Wang; Jinlu Sheng; Zhang Ruan; Yu Hua; Rui Zhang (Ocean Engineering, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Snakehead vesiculovirus (SHVV) leader RNA interacts with host antiviral factors RPS8 and L13a and promotes virus replication - Yan Ji; Rui Cheng; Xuan Zhou; Jiaqi Zhang; Xiaodan Liu; Suhong Sheng; Chi Zhang (Fish & Shellfish Immunology, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Entomopathogenic fungal-derived metabolites alter innate immunity and gut microbiota in the migratory locust - Wei Zhang; Chen Jia; Lian-Sheng Zang; Maiqun Gu; Rui Zhang; Ioannis Eleftherianos; Amr A. Mohamed (Journal of Pest Science, 2024)

Probabilistic assessment of seismic earth pressure against backfills with a nonlinear failure criterion - Rui Zhang; Xiangqian Sheng; Wenliang Fan (Soil Dynamics and Earthquake Engineering, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Excitation force on a pump-jet propeller: The clocking effect of pre-swirl stator - Yu Zhang; Jieting Han; Sheng Ji; Rui Wu; Bin Huang; Dahai Zhang; Dazhuan Wu (Ocean Engineering, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Influence of extractable organic components on shale wettability: Dongyuemiao member of Jurassic Ziliujing formation in the Fuxing area, Eastern Sichuan Basin - Weihang Zhang; Rui Yang; Zhiliang He; Hanyong Bao; Hui Yu; Shuling Xiong; Yuanjia Han; Qinhong Hu; Sheng He (Marine and Petroleum Geology, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Soil arching in ground with tunnel: Effect of distance between tunnel and trapdoor - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Hao Xiong; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

A single-site porphyrin (Cu)-based COF electrocatalyst for the electrochemical detection of gallic acid sensitively - Mei-Jie Wei; Jing Li; Ze-Qi Wei; Sheng-Feng Zhang; Zhong-Xia Wang; Heng-Ye Li; Rui Zhang; Fen-Ying Kong; Wei Wang (Analytica Chimica Acta, 2023)

Investigation of the soil arching evolution in the ground with or without a tunnel - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Tai-Feng Zhu; Guoping Lei; Xiang-Sheng Chen (Transportation Geotechnics, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

DEM study on evolution of soil arching in a deep trapdoor in seismic shaking conditions - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin; Yuan-Jun Jiang; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Transient analyses for China initiative Accelerator Driven System using the extended BELLA code - Guan Wang; Janne Wallenius; Rui Yu; Wei Jiang; Lu Zhang; Xin Sheng; Di Yun; Long Gu (Annals of Nuclear Energy, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Formation of giant copper deposits in Tibet driven by tearing of the subducted Indian plate - Zengqian Hou; Rui Wang; Haijiang Zhang; Yuanchuan Zheng; Sheng Jin; Hans Thybo; Roberto F. Weinberg; Bo Xu; Zhiming Yang; Ao-Wei Hao; Lei Gao; Letian Zhang (Earth-Science Reviews, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Single-stage object detector with local binary pattern for remote sensing images - Kexue Zhou; Min Zhang; Sheng Lin; Rui Zhang; Hai Wang (International Journal of Remote Sensing, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Differential effects of petroleum-based and bio-based microplastics on anaerobic digestion: A review - Zezhou Shang; Rui Wang; Xiyi Zhang; Yongle Tu; Chenjing Sheng; Huan Yuan; Lei Wen; Yulu Li; Jing Zhang; Xiaojiao Wang; Gaihe Yang; Yongzhong Feng; et al. (Science of The Total Environment, 2023)

Deep Learning-Assisted Quantitative Susceptibility Mapping as a Tool for Grading and Molecular Subtyping of Gliomas - Wenting Rui; Shengjie Zhang; Huidong Shi; Yaru Sheng; Fengping Zhu; YiDi Yao; Xiang Chen; Haixia Cheng; Yong Zhang; Ababikere Aili; Zhenwei Yao; Xiao-Yong Zhang; et al. (Phenomics, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

A novel solvent system of polyamides achieves new application in ZIBs by aggregation induced Lewis acid-base centers - Murong Xi; Zhenjie Liu; Rui Sheng; Jiafeng Zhu; Yong Guo; Juan Ding; Xingchao Wang; Yue Zhang; Lei Wang; Zhipeng Sun; Wenjun Zhang; Jiulin Wang; et al. (Chemical Engineering Journal, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Transcriptomic analysis of juvenile cobia in response to hypoxic stress - Jian-Sheng Huang; Zhi-Xiong Guo; Jian-Dong Zhang; Wei-Zheng Wang; Zhong-Liang Wang; Rui-Tao Xie; Eric Amenyogbe; Gang Chen (Aquaculture International, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Experimental investigation of thermodynamic and kinetic behaviors from water vapor adsorption on four typical clay minerals - Shuling Xiong; Manfei Chen; Hui Yu; Weihang Zhang; Qinhong Hu; Sheng He; Rui Yang (Gas Science and Engineering, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

The impact of natural disasters on household debt: evidence from 2014 China family panel studies - Rui Zhang; Sheng Xu; Ruidong Sun (Environmental Science and Pollution Research, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Xanthophyll cycle-related non-photochemical quenching protects Sargassum thunbergii from high light-induced photoinhibition - Guo-Ning Nan; Xiao-Qun Zhou; Xiu-Mei Zhang; Quan-Sheng Zhang; Zi-Min Hu; Rui-Ping Huang; Di Zhang (Frontiers in Marine Science, 2022)
As a common macroalga living in the intertidal zone, Sargassum thunbergii (Sargassaceae, Phaeophyta) is often exposed to drastic changes in solar photosynthetically active radiation during a diurnal cycle; thus, the potential photosynthetic adaptation processes deserve attention. In this work, we examined the photosynthetic performance and xanthophyll cycle activity of this alga in response to high light (1,200 μmol photons m –2 s –1 , the average in-situ light intensity at noon) by using chlorophyll fluorescence and high-performance liquid chromatography (HPLC). On exposure to high light, a rapid decrease in the effective quantum yield of photosystem II (PSII) (Y(II)) occurred, indicating down-regulation of PSII activity; a corresponding increase in non-photochemical quenching (NPQ) indicated the existence of energy-dissipating cycles. After turning off the light, Y(II) gradually increased to 0.7, accompanied by a decrease in NPQ. However, no complete recovery of NPQ was observed, and its value remained at ≈4, even after an 80-min dark treatment. The size of the xanthophyll cycle pigments pool was quantified using HPLC and was found to be ≈16 mol mol −1 Chl a × 100. The activity of the xanthophyll cycle, characterized by a de-epoxidation state (DPS), could reach up to ≈0.5. Such a large pigments pool and rapid accumulation of zeaxanthin may allow S. thunbergii to induce high values of NPQ (≈10). These results were further complemented by inhibitor (dithiothreitol, DTT) and pre-illumination experiments showing that (1) both NPQ and the xanthophyll cycle could be inhibited by DTT, and there was always a strong positive correlation between NPQ and DPS; (2) the previously formed antheraxanthin exhibited a long retention time and a slow epoxidation; and (3) the long retention of antheraxanthin contributed to a rapid accumulation of zeaxanthin. In conclusion, our present study demonstrated that xanthophyll cycle-induced NPQ can significantly protect S. thunbergii from light fluctuations in the intertidal zone.

Neglected skin-associated microbial communities: a unique immune defense strategy of Bufo raddei under environmental heavy metal pollution - Rui Su; Sheng Zhang; Xueying Zhang; Shengnan Wang; Wenya Zhang (Environmental Science and Pollution Research, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Acacetin antagonized lipotoxicity in pancreatic β-cells via ameliorating oxidative stress and endoplasmic reticulum stress - Ning Wang; Qing Gao; Jie Shi; Chen Yulan; Weimeng Ji; Xiumei Sheng; Rui Zhang (Molecular Biology Reports, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

Evaluation of leachate production and level in municipal solid waste landfills considering secondary compression - Han Ke; Chen Sheng Zhang; Jie Hu; Rui Qin; Yun Min Chen; Ji Wu Lan (Environmental Science and Pollution Research, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form - Honghua He; Zekun Zhang; Qi Peng; Chao Chang; Rui Su; Xiao Cheng; Yingxin Li; Jiayin Pang; Sheng Du; Hans Lambers (Plant and Soil, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Impacts of anthropogenic disturbances on microbial community of coastal waters in Shenzhen, South China - Rui Zhang; Wen-chao Liu; Yu Liu; Hong-lian Zhang; Zhi-hui Zhao; Ling-yun Zou; Yu-chun Shen; Wen-Sheng Lan (Ecotoxicology, 2021)

Numerical Investigation of the Characteristics of Erosion in a Centrifugal Pump for Transporting Dilute Particle-Laden Flows - Rui-Jie Zhao; You-Long Zhao; De-Sheng Zhang; Yan Li; Lin-Lin Geng (Journal of Marine Science and Engineering, 2021)
Erosion in centrifugal pumps for transporting flows with dilute particles is a main pump failure problem in many engineering processes. A numerical model combining the computational fluid dynamics (CFD) and Discrete Element Method (DEM) is applied to simulate erosion in a centrifugal pump. Different models of the liquid-solid inter-phase forces are implemented, and the particle-turbulence interaction is also defined. The inertial particles considered in this work are monodisperse and have finite size. The numerical results are validated by comparing the results with a series of experimental data. Then, the effects of particle volume fraction, size, and shape on the pump erosion are estimated in the simulations. The results demonstrate that severe erosive areas are located near the inlet and outlet of the pressure side of the impeller blade, the middle region of the blade, the corners of the shroud and hub of the impeller adjoining to the pressure side of the blade, and the volute near the pump tongue. Among these locations, the maximum erosion occurs near the inlet of the pressure side of the blade. Erosion mitigation occurs under the situation where more particles accumulate in the near-wall region of the eroded surface, forming a buffering layer. The relationship between the particle size and the erosion is nonlinear, and the 1 mm particle causes the maximum pump erosion. The sharp particles cause more severe erosion in the pump because both the frequency of particle-wall collisions and the impact angle increase with the increasing sharpness of the particle.

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Efficient generation of GHR knockout Bama minipig fibroblast cells using CRISPR/Cas9-mediated gene editing - Rui Wang; Jian-Ying Zhang; Ke-Huan Lu; Sheng-Sheng Lu; Xiang-Xing Zhu (In Vitro Cellular & Developmental Biology - Animal, 2019)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Micro-failure Analysis of Direct and Flat Loading Brazilian Tensile Tests - Yan-Sheng Wang; Jian-Hui Deng; Lin-Rui Li; Zheng-Hu Zhang (Rock Mechanics and Rock Engineering, 2019)

Chemical constituents from the leaves of Melia azedarach - Jin Zeng; Rui-Jing Ma; Ling Wang; Sheng-Nan Zhang; Hong-Zhi Song; Yang Yang; Qin-Gang Tan (Natural Product Research, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

QsvR integrates into quorum sensing circuit to control Vibrio parahaemolyticus virulence - Yiquan Zhang; Linghui Hu; Yue Qiu; George Osei‐Adjei; Hao Tang; Ying Zhang; Rui Zhang; Xiumei Sheng; Shungao Xu; Wenhui Yang; Huiying Yang; Zhe Yin; et al. (Environmental Microbiology, 2019)
Summary Vibrio parahaemolyticus , the leading cause of seafood‐associated gastroenteritis worldwide, requires the two type‐III secretion systems (T3SS1 and T3SS2) and a thermostable direct hemolysin (encoded by tdh1 and tdh2 ) for full virulence. The tdh genes and the T3SS2 gene cluster constitute an 80 kb pathogenicity island known as Vp‐PAI located on the chromosome II. Expression of T3SS1 and Vp‐PAI is regulated in a quorum sensing (QS)‐dependent manner but its detailed mechanisms remain unknown. Herein, we show that three factors (QS regulators AphA and OpaR and an AraC‐type transcriptional regulator QsvR) form a complex regulatory network to control the expression of T3SS1 and Vp‐PAI genes. At low cell density (LCD), whereas Vp‐PAI expression is repressed, T3SS1 genes are induced by AphA, which directly binds (an operator region of) the exsBAD‐vscBCD operon. At high cell density (HCD), the bacterium turns off T3SS1 expression by replacing AphA with OpaR, triggering the induction of Vp‐PAI. Furthermore, QsvR binds to the regulatory regions of all the tested T3SS1 and Vp‐PAI genes to activate their transcription at HCD. Taken together, our data highlight how multiple QS regulators contribute to the pathogenicity of V. parahaemolyticus by precisely controlling the expression of major virulence determinants during different stages of growth.

Transgenic Rice Overexperessing a Tomato Mitochondrial Phosphate Transporter, SlMPT3;1, Promotes Phosphate Uptake and Increases Grain Yield - Guo-hong Yu; Sheng-cai Huang; Rui He; Ying-zhang Li; Xian-guo Cheng (Journal of Plant Biology, 2018)

Spatial patterns of interprovincial mountain geographical names in China and implications for regional governance - Sheng-rui Zhang; Ying-jie Wang; Hong-run Ju; Tong-yan Zhang; Dai-chao Li; Lei Fang; Ying-ying Wang (Journal of Mountain Science, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Photoperiodism dynamics during the domestication and improvement of soybean - Sheng-Rui Zhang; Huan Wang; Zhongyu Wang; Yao Ren; Lifang Niu; Jun Liu; Bin Liu (Science China Life Sciences, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Paenibacillus oryzisoli sp. nov., isolated from the rhizosphere of rice - Jun Zhang; Xiao-Tong Ma; Jun-Sheng Gao; Cai-Wen Zhang; Juan-Juan Zhao; Rui-Jie Zhang; Li-An Ma; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)

Investigating the Effect of Tissue Size on Mycelial Growth of Seven Mushroom Species by Using a Novel Device for Precise Tissue Isolation - Sheng-Rong Liu; Wei-Rui Zhang; Ai-Ping Chen; Yun-Bo Kuang (Indian Journal of Microbiology, 2016)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Village network centrality in rural tourism destination: A case from Yesanpo tourism area, China - Rui-ying Zhang; Jian-chao Xi; Shou-kun Wang; Xin-ge Wang; Quan-sheng Ge (Journal of Mountain Science, 2015)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Consumption of hydrogen-rich water alleviates renal injury in spontaneous hypertensive rats - Hai-Guang Xin; Bei-Bei Zhang; Zhi-Qin Wu; Xiao-Feng Hang; Wen-Sheng Xu; Wu Ni; Rui-Qi Zhang; Xiao-Hui Miao (Molecular and Cellular Biochemistry, 2014)

Genome-Wide Identification, Classification, Expression Profiling, and SSR Marker Development of the MADS-Box Gene Family in Citrus - Xiao-Jin Hou; Sheng-Rui Liu; Muhammad Rehman Gul Khan; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology Reporter, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Complete disassociation of adult pancreas into viable single cells through cold trypsin-EDTA digestion - Dan Li; Shi-yun Peng; Zhen-wu Zhang; Rui-cheng Feng; Lu Li; Jie Liang; Sheng Tai; Chun-bo Teng (Journal of Zhejiang University-SCIENCE B, 2013)

Cytoplasmic diversity in Brassica rapa L. investigated by mitochondrial markers - Rui-Jie Zhang; Sheng-Wu Hu; Jin-Qiang Yan; Gen-Lou Sun (Genetic Resources and Crop Evolution, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Sterols and triterpenoids from the spores of Ganoderma lucidum - Chuan-Rui Zhang; Sheng-Ping Yang; Jian-Min Yue (Natural Product Research, 2008)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)